Estimation of Noise Induced by Multimode Optical Fibers in Optical Sensor Systems - Bartula, Renata J.; Conrad, Benjamin L.; Sanders, Scott T. (My University, 2008)
We present evidence of MMF noise and introduce an algorithm that predicts the amplitude of the noise as a function of parameters such as core diameter, fiber length, and spectral resolution.
Presented Thursday 16 August 2007 at the Gordon Research Conference on Laser Diagnostics for Combustion, Oxford, United Kingdom.